(untitled) - Takemiya, Hirokazu (London, 2005)
The environmental vibrations, caused by train/traffic, construction activities and factory operation, and other man-made sources are being investigated, globally, for their prediction, control and mitigation, basically, to improve the quality of life in modern society, operation of sensitive machines and high-tech production. The Japanese Geotechnical Society, Architectural Institute of Japan, Japan Society of Civil Engineering, Chinese Society for Vibration Engineering and Okayama University organised an International Symposium on Environmental Vibrations: prediction, monitoring and evaluation (ISVE2005) during September, 2005. In order to record this international exchange of experience, knowledge and research discussed during the conference and make it available to the research community and working professionals, the proceedings are presented in this book. It contains the invited and regular papers written and presented by widely respected academic professionals and engineering specialists. Thus, the book describes the current state-of-the art in addition to the expertises and practices in the related fields, including Wave propagation in soils; Soil dynamics; Soil-structure dynamic interaction; Field measurement of environmental vibration caused by traffic, construction, machines, wind, etc.; Monitoring of environmental vibrations; Development of vibration mitigation measures; Evaluation of environmental vibrations; Vibration effects on human perception; Vibration effects on high-precision machines
Dao động cơ học
Keywords: Vibration